Tetramethylpyrazine Alleviates Behavioral and Psychological Symptoms of Dementia Through Facilitating Hippocampal Synaptic Plasticity in Rats With Chronic Cerebral Hypoperfusion - Tan, Zihu; Qiu, Jing; Zhang, Yuting; Yang, Qiong; Yin, Xixi; Li, Jia; Liu, Guangya; Li, Hengfei; Yang, Guang (Frontiers in Neuroscience, 2021)
Behavioral and psychological symptoms of dementia (BPSD) ubiquitously disturb all patients with dementia at some point in the disease course. Though a plethora of non-pharmacological and pharmacological methods target relieving BPSD have been developed, the therapeutic effect is still far from ideal. Here, a rat BPSD model, combined the physiological changes with mental insults, was successfully established. Meanwhile, our results indicated that TMP attenuated anxious behavior using elevated plus maze (EPM) test, ameliorated recognitive ability and sociability through novel object recognition test (NORT) and social interaction test (SIT), and improved learning and memory impairments via Barnes maze in rats with bilateral common carotid arteries occlusion (BCCAO) plus chronic restraint stress (CRS). Given that hippocampus chronic cerebral hypoperfusion (CCH) always causes damage to hippocampus and majority of cognitive impairments, behaviors and stress response are association with pathology in hippocampus including anxiety and depression, we paid attention to investigate the role of hippocampus in BPSD. Our results indicated that Tetramethylpyrazine (TMP) attenuated anxiety and ameliorated recognitive ability, sociability, learning and memory impairments due to alleviating dendritic and spine deficits, and upregulating the expression of synapse-related proteins (including PSD95, SYN, GAP43, SYP) in hippocampus. And, the underlying mechanism was that TMP could activate TrkB/ERK/CREB signaling pathway to promote synaptic remodeling in vivo and in vitro. Mechanically, the present study enlarges the therapeutic scope of TMP in neurodegenerative disorders, and provide basic knowledge and feasible candidate for treating BPSD, particularly for vascular dementia.